Study on the diagnosis of rabbit VX2 esophageal cancer and stent‐therapy efficacy based on multiphoton microscopy. Issue 2 (12th February 2015) - Ma, Limei; Huang, Xiaoyang; Wang, Xiaohong; Zhang, Yong; Liu, Li; sheng, Yu; Fan, Zhining
Summary Histopathology is the gold standard for diagnosis of esophageal carcinoma. Based on two photon excited fluorescence (TPEF) and second harmonic generation (SHG), multiphoton microscopy (MPM) has become a novel optical tool adjunct to current histopathological techniques without any exogenous contrast agents. We thus investigated the potential of using TPEF and SHG techniques for differentiating cancer tissues from cancer tissues after paclitaxel‐eluting stent implantation and normal esophageal tissues which are fresh and unstained without dying from the VX2 esophageal carcinoma rabbit models. Comparisons were made between MPM imaging and gold standard sections for each specimen stained with hematoxylin‐eosin (H&E). Our results indicated that the MPM imaging technique could identify and distinguish among normal esophageal tissues, cancer tissues, as well as cancer tissues after stent implantation. Therefore, MPM potentially offers a powerful tool to not only diagnose esophageal cancer but also monitor stent‐therapy efficacy. SCANNING 37:152–157, 2015. © 2015 Wiley Periodicals, Inc.